Using optimized monochromatic energy dispersive x-ray fluorescence to determine the cadmium concentration in cacao and soil samples - Dekeyrel, Jesse; Atkinson, Rachel; Chavez, Eduardo; Silva, Mayesse Aparecida da; Idarraga-Castaño, Orlando; Pulleman, Mirjam; Smolders, Erik (Elsevier, 2024)
Following the implementation of food safety limits on cadmium (Cd) in cacao products, there has been a growing demand for monitoring Cd in cacao tissues and soils. Traditional methods like acid digestion followed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) are time-consuming and costly. X-ray Fluorescence is an alternative technique that offers advantages in terms of speed, cost, ease of use and less environmental impact. However, to date, relatively high detection limits have impeded its application for food safety limits. This study examines a Monochromatic Energy Dispersive X-ray Fluorescence (MEDXRF) method optimized for Cd analysis as an alternative to ICP-MS. Using a measurement time of 200 s, the average limit of quantification (LOQ) was 0.178 mg Cd kg−1 for biological samples and 0.205 mg Cd kg−1 for soil samples. A strong correlation (y = 1.013 x + 0.003, R2 = 0.984) with ICP-MS results was found for 95 bean, 16 cacao liquor, 75 leaf, and 91 soil samples. The coefficient of variation (CV) among three replicates was below the threshold value of 15 % for most samples with Cd concentrations above the reported LOQ values. Additionally, a significant difference in CV was obtained between soils sieved over 500 μm (median 8.2 %) or 2 mm (median 9.8 %). However, no significant difference in CV was observed between 500 μm unpeeled beans and cocoa liquor with particle size of 20 μm. Based on our data, the proposed procedure is to analyze three replicates for 200 s with a sample size of 500 μm. The optimized MEDXRF technique offers important advantages in terms of cost-effectiveness and efficiency of routine Cd monitoring in the cacao supply chain, large-scale screening, and scientific research, and could be extended to other crops and heavy metals that are subject to food safety regulation at low concentrations.